Effect of Huanglongbing or Greening Disease on Orange Juice Quality, a Review - Dala-Paula, Bruno M.; Plotto, Anne; Bai, Jinhe; Manthey, John A.; Baldwin, Elizabeth A.; Ferrarezi, Rhuanito S.; Gloria, Maria Beatriz A. (Frontiers in Plant Science, 2019)
Huanglongbing (HLB) or citrus greening disease is the most severe citrus disease, devastating the industry worldwide. The presumed causal bacterial agent Candidatus Liberibacter spp. affects tree health as well as fruit development, ripening and quality of citrus fruit and juice. Fruit from infected trees can be either symptomatic or asymptomatic. Symptomatic fruit are small, asymmetrical and greener than healthy fruit. Furthermore, symptomatic fruit show higher titratable acidity and lower soluble solids, solids/acids ratio, total sugars and malic acid levels, lower ethyl butanoate, valencene, decanal and other ethyl esters, straight-chain aldehydes and sesquiterpenes, but higher in many monoterpenes compared to healthy and asymptomatic fruit. The disease also causes an increase in secondary metabolites in the orange peel and pulp, including hydroxycinnamic acids, limonin, nomilin, narirutin and hesperidin. Resulting from these chemical changes, juice made from symptomatic fruit is described as distinctly bitter, sour, salty/umami, metallic, musty, and lacking in sweetness and fruity/orange flavor. Those effects are reported in both Valencia and Hamlin oranges, two cultivars that are commercially processed for juice. The presumed HLB pathogen remains unconfirmed and its management is challenging due to the unpredictable latency times for symptoms after the tree has become infected, and the lack of effective curative treatment methods. When present, disease management depends on incidence rate, and relies on vector control, tree eradication, nutritional programs and use of plant varieties with increased tolerance. Earlier research showed that HLB-induced off-flavor was not detectable in juice made with up to 25% symptomatic fruit. In some production regions, it is increasingly difficult to find fruit not showing HLB symptoms. This review focuses on the effects of HLB on orange juice quality regarding chemical, physicochemical and biochemical characteristics, including levels of sugars, organic acids, secondary metabolites, levels and profiles of amino acids, bioactive amines, volatile compounds and sensory characteristics, as well as future research needs.